Electrical spin injection and detection in semimetallic Bi and Bi-Pb films - Lee, Kyoung-Il; Roh, Jong Wook; Chang, Joonyeon; Han, Suk-Hee; Shin, Kyung-Ho; Jeung, Won Yong; Johnson, Mark; Lee, Wooyoung (AMER PHYSICAL SOC, 2009)
The spin injection technique is extended to semimetal bismuth samples in a lateral spin valve geometry. We study spin injection, diffusion, and detection in a material system where a small change in sample stoichiometry results in a large change in the electronic and spin dependent transport properties of the nonmagnetic material. Measurements of magnetoresistance, using a magnetic field applied in the sample plane, as well as the Hanle effect, using a field applied perpendicular to the sample plane, are reported. We demonstrate two remarkable results: (i) a spin diffusion length of 230 mu m (T=2 K) in a BiPb sample with temperature dependent resistivity, rho(T), which decreases with decreasing T is the longest known value in a thin film; (ii) the interfacial spin polarization is 10% in BiPb samples with decreasing rho(T) and an order of magnitude smaller (0.8%) in Bi samples where rho(T) increases with decreasing T.
Keywords: LARGE MAGNETORESISTANCE; ELECTRONIC MEASUREMENT; TRANSPORT-PROPERTIES; BISMUTH; ORBIT